The Role Of School Anti-Drug Peer Groups In Raising Awareness About Drug Dangers At SMAN 4 Of Bengkulu City - Haryadi, Dedi; Narti , Sri; Maryaningsih, Maryaningsih (Social Sciences Journal, 2024)
This research aims to find out the role of School Anti-Drug Peer Groups in socializing the dangers of drugs in the school environment at SMAN 4 Bengkulu City. The theory used in this research is Jeager's (1997) Socialization theory. In this theory there are 2 types of socialization. Among them are Repressive Socialization and Participatory Socialization. This study used qualitative research methods. In this study there were 8 informants who were determined based on purposive sampling techniques. The research results show that the role of SANS peers at SMAN 4 of Bengkulu City in participatory socialization is very significant, especially in disseminating information about the dangers of drugs at SMAN 4 of Bengkulu City. SANS members, as students' peers, use a personal and relevant approach to convey messages about the dangers of drugs. They not only provide information, but also actively engage students in activities such as group discussions, role plays, and interactive presentations. Thus, the role of SANS (peers) can be categorized as running optimally in socializing the dangers of drugs at SMAN 4 of Bengkulu City. SANS (peers) provides opportunities for students to learn, contribute, and feel the direct impact of anti-drug socialization, thereby helping to increase students' awareness and understanding of the risks of drug abuse. This is also fully supported by SMAN 4 of Bengkulu City, as can be seen from the collaboration between the Principal, staff and SANS administrators, the school has developed clear Standard Operating Procedures (SOP) in enforcing drug regulations.